2000
DOI: 10.2166/wst.2000.0265
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and estrogen mimics contamination in water and the role of sewage treatment

Abstract: The yeast estrogen screen was applied to sewage treatment process waters to identify the presence of estrogenic activity and to investigate the fate and behavior of estrogenic substances through treatment. Hydrophobic fractions in the water phase were extracted and concentrated using C18 cartridges for the effective extraction of 17β-estradiol (E2) and other estrogen mimics. Clear dose-dependent elevation in the synthesis of β-galactosidase in the yeast screen was observed with all the samples tested, demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 0 publications
4
83
1
4
Order By: Relevance
“…However, transformations of E2 toE1 occurred in samples which had not been sterilized and this was attributed to biological inter-conversion under anaerobic conditions possibly catalysed by other biological conversions. Higher levels ofE1 were observed in the sludge entering an anaerobic digester than leaving in the treated sludge suggesting the conversion of E1 to E2 [35] providing further potential evidence of biotransformation. The de-conjugation of E1-3S, and thus its conversion to E1, appeared to be unaffected by temperature as the percent removal range has a maximum of 7% between thermophilic and mesophilic temperatures for the equivalent sludge types (Table 2).…”
Section: Effect Of Temperature On the Removal Of Steroid Estrogensmentioning
confidence: 96%
“…However, transformations of E2 toE1 occurred in samples which had not been sterilized and this was attributed to biological inter-conversion under anaerobic conditions possibly catalysed by other biological conversions. Higher levels ofE1 were observed in the sludge entering an anaerobic digester than leaving in the treated sludge suggesting the conversion of E1 to E2 [35] providing further potential evidence of biotransformation. The de-conjugation of E1-3S, and thus its conversion to E1, appeared to be unaffected by temperature as the percent removal range has a maximum of 7% between thermophilic and mesophilic temperatures for the equivalent sludge types (Table 2).…”
Section: Effect Of Temperature On the Removal Of Steroid Estrogensmentioning
confidence: 96%
“…Because only 1-2% of administered EE2 is transformed to E1, E2, or E3 (Ranney 1977) and, compared with natural E2 excretion, the amount of E2 in pharmaceutical usage is <5% (Christensen 1998), the higher relative abundance of natural estrogens should be due to human excretions (Zhou et al 2011). A study in Japan has also concluded that human estrogens are the major estrogenic compounds in sewage and effluent (Matsui et al 2000). In effluent from the present study, the relative abundance of E1 and EE2 in excess of 70% revealed lower removal of E1 and EE2.…”
Section: Levels Of Steroid Estrogens In Wwtp Influent and Effluentmentioning
confidence: 99%
“…A study of mass balance of estrogens in sewage treatment works (STW) in Germany demonstrated that most of the estrogenic activity in the wastewater was biodegraded during treatment rather than adsorbed onto suspended solids (Korner et al, 2000). In a study of Japanese STWs by Matsui et al (2000), it was shown that 10 % removal of E2 occurred across the primary sedimentation, 87 % across the nitrifying activated sludge and a further 22 % removal across the tertiary sand filters. The overall removal of 87 % was reported.…”
Section: Introductionmentioning
confidence: 99%